Improving Inventory Turnover In A Fiber Optics Manufacturing Project - Huang, Hai (2014)
High inventory has been one of the unstable operation factors in fiber optics manufacturing projects in VTR Penang, a contract manufacture. This case study looks into the particularly high inventory turnover days issue encountered in a newly launched fiber optics project-MI5K project in VTR. MI5K is a high mix low volume manufacturing project with 60 days inventory turnover target， however the actual performance is 82 days. The study begins with understanding the existing workflow together with the business intelligence system.